The Historiography of Philosophy in Lithuania during Soviet Period - Kabelka, Gintaras (Studia z Historii Filozofii, 2019)
This article attempts to briefly present the most important research in the historiography of philosophy in Lithuania during the Soviet period, to explicate their methodological structure displaying the applied elements of philosophical historical explanations. The Marxist methodology In Lithuania structures the field of inquiry by means of vertical and horizontal reductions. The first one is founded on the causal relations between the basis and the superstructure, the second – on the application of the Marxist categories. Alongside the Marxism-based methodological principles considered compulsory for the investigations, there were some instances of using non-Marxist methodology. R. Plečkaitis’s works will be treated in terms of the applied methodological approach to the history of problems. The most important element of his research is the historical reconstruction of a problematic situation as a constellation of theoretical elements motivating the creation of a new theory.